The application of group work activities to improve speaking skills for 10th grade students at a Bac Ninh high school - Nguyễn, Thị Trang (2020)
The study was carried out with an attempt to investigate the application of group work towards enhancing grade 10 students’ speaking skill. The subjects participating in the research were 40 EFL students studying in the same class at a high school in Bac Ninh province. To achieve the desired aims of the study, an action research was carried out. Survey questionnaires for students and learning logs were used as the major instruments to collect data about students’ challenges in developing their speaking skill and the impacts of group work implementation on students’ speaking ability. The results of the study showed that group work has positive influence on the development of students’ speaking skill and has the potential to help students deal with some challenges that they may encounter in speaking lessons.